Effects of a novel anti-exospore monoclonal antibody on microsporidial development in vitro - Sak, B; Saková, K; Ditrich, O (Parasitology research, 2004)
The possible role of humoral antibodies in the immune response to microsporidiosis was studied using a novel anti-exospore monoclonal antibody (MAb) P5/H1 which recognised Encephalitozoon cuniculi. The effect of the P5/H1 MAb on microsporidial growth in vitro resulted in a reduction of the numbers of E. cuniculi spores in a Vero E6 cell-line culture. This reduction in the number of infected cells and the decrease of intracellular spores in infected cells was found when MAb P5/H1 was present in cultures, compared to cultures with an irrelevant isotype control MAb. Moreover, the presence of P5/H1 MAb increased the number of phagocytosed spores in macrophage cultures, and increased the activation of macrophages measured by nitrite oxide production. These results suggest a possible partial role of specific humoral antibodies in the protection against E. cuniculi infection.
Keywords: Animals; Chlorocebus aethiops; Female; Interferon-gamma; makrofágy; ženské pohlaví; Spores, Protozoan; antigeny protozoální; Vero Cells; Antibodies, Monoclonal; Macrophages; Vero buňky; Mice; Sensitivity and Specificity; Mice, Inbred BALB C; senzitivita a specificita; kultivované buňky; myši; interferon gama; Encephalitozoon cuniculi; Cells, Cultured; Antigens, Protozoan; protilátky protozoální; Antibodies, Protozoan; myši inbrední BALB C; Antibody Specificity; Cercopithecus aethiops; monoklonální protilátky; specificita protilátek; zvířata; spory protozoální